Design of dualband linear array antenna by circular microstrip patch antenna / Noor Adlina Mohd Zulkhairi - Mohd Zulkhairi, Noor Adlina (2012)
This paper describes the performance evaluation of 2x2 linear array circular patch antenna. This antenna has been designed on Flame Retardant 4 (FR-4) printed circuit board, dielectric substrate Er= 4.7. it has been simulated by using Computer Simulation Technology (Csn 2009 software. It has been simulated based on 500 characteristic impedance for the transmission line model. After simulation, this antenna design have two suitable frequency that is its return loss is below than -1 0dB. Linear array also have been used in order to increase gain and directivity. Performance of return loss (S11), Voltage Standing Wave Ratio (VSWR) and gain have been analyzed. Their performances also have been compared between simulation and measurement result. By using array, it have been approved that performance of gain and directivity are increase.